Assessing the integration of forward osmosis and anaerobic digestion for simultaneous wastewater treatment and resource recovery. (July 2018) - Ansari, Ashley J.; Hai, Faisal I.; Price, William E.; Ngo, Huu H.; Guo, Wenshan; Nghiem, Long D.
Highlights: No negative effect on CH4 production at 10 folds wastewater pre-concentration. At 90% water recovery, CH4 production using NaOAc was 10% more than NaCl as DS. The unit cost of methane production was highly sensitive to the reverse salt flux. The unit cost of methane production using NaOAc was slightly lower than NaCl. Membrane fouling was limited to surface deposition and was readily removed by flushing. Abstract: This study assessed the performance and key challenges associated with the integration of forward osmosis (FO) and anaerobic digestion for wastewater treatment and resource recovery. Using a thin film composite polyamide FO membrane, maximising the pre-concentration factor (i.e. system water recovery) resulted in the enrichment of organics and salinity in wastewater. Biomethane potential evaluation indicated that methane production increased correspondingly with the FO pre-concentration factor due to the organic retention in the feed solution. At 90% water recovery, about 10% more methane was produced when using NaOAc compared with NaCl because of the contribution of biodegradable reverse NaOAc flux. No negative impact on anaerobic digestion was observed when wastewater was pre-concentrated ten-fold (90% water recovery) for both draw solutes. Interestingly, the unit cost of methane production using NaOAc was slightly lower than NaCl due to the lower reverse solute flux of NaOAc, although NaCl is a much cheaper chemical.